Application of Polymeric Micelles for Drug and Gene Delivery - Emi Haladjova; Stanislav Rangelov (MDPI AG, 2024)
Polymeric micelles have been extensively studied because of their ability to transfer biologically active agents, such as drugs and nucleic acids [...]